Unpacking the paradoxical impact of ethical leadership on employees’ pro-social rule-breaking behavior: The interplay of employees’ psychological capital and moral identity - Ahmed, Mushtaq; Ishfaq Khan, Muhammad (PloS one, 2024)
This study delves into the complex dynamics of ethical leadership’s influence on employees’ pro-social rule-breaking behavior, taking into account the mediating role of psychological capital and the moderating effect of moral identity. Using data collected from nursing staff in Pakistani hospitals and analyzed through PLS SEM, the study yielded unexpected results. Contrary to the initial hypotheses, the findings reveal a positive relationship between ethical leadership and employees’ pro-social rule-breaking behavior within organizational settings. Furthermore, the study identifies psychological capital as a key mediator in this relationship, while moral identity emerges as a crucial moderator. These results challenge the conventional perception of ethical leadership as an exclusively positive form of leadership and underscore its unintended consequences. Moreover, they underscore the significance of employees’ psychological processes and individual differences in unraveling this paradoxical relationship. These results have the potential to reshape how organizations view ethical leadership and consider the unintended outcomes it may generate. Future research can build upon these findings to explore the boundaries and contextual factors that influence the effects of ethical leadership, ultimately contributing to a more comprehensive understanding of leadership dynamics in diverse organizational settings.